Health, human rights, and the conduct of clinical research within oppressed populations - Mills Edward J; Singh Sonal (BMC, 2007)
Abstract Background Clinical trials evaluating interventions for infectious diseases require enrolling participants that are vulnerable to infection. As clinical trials are conducted in increasingly vulnerable populations, issues of protection of these populations become challenging. In settings where populations are forseeably oppressed, the conduct of research requires considerations that go beyond common ethical concerns and into issues of international human rights law. Discussion Using examples of HIV prevention trials in Thailand, hepatitis-E prevention trials in Nepal and malaria therapeutic trials in Burma (Myanmar), we address the inadequacies of current ethical guidelines when conducting research within oppressed populations. We review existing legislature in the United States and United Kingdom that may be used against foreign investigators if trial hardships exist. We conclude by making considerations for research conducted within oppressed populations.